Sexuality and climacteric: a comprehensive approach - Belardo, María Alejandra; Gelin, Marina (Revista del Hospital Italiano de Buenos Aires, 2016)
When we talk about human sexuality, we know that we are talking about a complex and changing interaction between biological and socioemotional factors, which are highly influenced by society, family, religion and cultural norms. This can be seen in men and women especially in women Sexuality is an intuitive concept difficult to define. According to the World Health Organization, it is defined as “A state of physical, emotional, mental and social well being related to sexuality, which is not merely the absence of disease, dysfunction or disabilityˮ. It is a definition that takes into account several concepts, all very important. Sexual response is a series of neurophysiological, hemodynamic and hormonal changes involving the whole body. While similar in both sexes, women are not always the onset and progression correlate systematically or linearly as in men. And that intriguing evolution of the female sexual response, the difficulty of diagnosis of “female sexual dysfunctionˮ. We could summarize it in “a group of disorders in which the physiological or psychological problems impede participation or satisfaction in sexual activities; which results in the inability of a person to participate in a sexual relationship the way she or he would like to do itˮ16. Menopause is perceived by many women as to the end of sexuality, not only as the end of reproductive life. Sexual activity declines with age, and may be affected by a number of hormonal, psychological and sociocultural factors, but, for most women it continues to be important. We must understand that female sexual dysfunction, at any stage of life is multicausal and multidimensional. When approaching a patient, it is important to know all the factors that are involved, and which tools we have for deal with it. Classically, the therapeutic approach has consisted of psychological therapy and hormone therapy. However, we have to consider a recently approved drug by the FDA for the treatment of hypoactive sexual desire in women: Flibanserin. It is a psychotropic substance that acts on the mediators of sexual desire on the central nervous system favoring it.
Keywords: sexuality; climacteric; sexual response; hypoactive sexual desire